Waist-to-Hip Ratio and Body Mass Index as Predictors of Blood Pressure Elevation Among Adolescents: A Cross-Sectional Study - Frastiqa Fahrany; Lani Rahmadhani; Dedi Kurniawan; Ajak Ater (Health Frontiers: Multidisciplinary Journal for Health Professionals, 2026)
Hypertension in adolescence is an emerging public health concern, with central and general adiposity recognised as modifiable determinants of elevated blood pressure. This study examined the associations of waist-to-hip ratio (WHR) and body mass index (BMI) with blood pressure and evaluated their relative strength as predictors of elevated blood pressure among senior secondary school students in East Java, Indonesia. A cross-sectional observational study was conducted on 14 February 2025 at SMA Diponegoro Tumpang involving 72 students aged 15–18 years selected through simple random sampling. WHR, BMI, and blood pressure were measured using standardised procedures, and elevated blood pressure was classified according to the 2017 American Academy of Pediatrics guidelines. Chi-square tests and binary logistic regression were used to analyse associations and identify independent predictors after adjustment for age and sex. The participants had a mean age of 16.5 ± 0.9 years, and 58.3% were female. Elevated blood pressure was identified in 30.6% of students. Both WHR (OR = 5.14, 95% CI: 1.89–13.97, p < 0.001) and BMI (OR = 4.73, 95% CI: 1.77–12.64, p < 0.001) were significantly associated with elevated blood pressure. In multivariable analysis, WHR remained an independent predictor (adjusted OR = 4.21, 95% CI: 1.47–12.07, p = 0.007), whereas BMI was no longer significant after adjustment. These findings indicate that central adiposity, as measured by WHR, is a stronger predictor of elevated blood pressure than general adiposity in Indonesian adolescents and supports the inclusion of WHR screening in school-based cardiovascular risk prevention programmes.